Removal efficiency of acetaminophen and bisphenol a using ozonation procress - Nur Anis Ahmad Lutpi,1990-, author 521291; Muhamad Ali Muhammad Yuzir, supervisor 603302; Mohd. Razman Salim, supervisor 376503; Yong, Ee Ling, supervisor 640291; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Alam Sekitar))